Tackling Poverty in Northern Ghana - World Bank (World Bank, 2012)
Twenty years of rapid economic development in Ghana has done little, if anything, to reduce the historical North, South divide in standards of living. While rural development and urbanization have led to significant poverty reduction in the South, similar dynamics have been largely absent from Northern Ghana (or equivalently the North, defined as the sum of the administrative regions Upper West, Upper East, and the Northern region), which cover 40 percent of Ghana's land area. Between 1992 and 2006, the number of the poor declined by 2.5 million in the South and increased by 0.9 million in the North. In sharp contrast with the South, there was no significant decline in the proportion of poor in the population of the North. Ghana's success story in poverty reduction is the success story of its South. Finally, North-South migration should not be seen as detracting from the potential development of Northern Ghana. North-South migration is potentially a strong instrument for poverty alleviation. With the right human capital, many individuals could escape from poverty through migration to the dynamic South. This phenomenon however, remains marginal today. By the same token, greater North-South migration will most likely be a consequence of any development in Northern Ghana, at least for some decades. Indeed, with greater economic integration and better public service provision, the probability that residents of Northern Ghana will benefit from migration will tremendously increase, thus their incentive to migrate. Hence, one should not expect lower migration pressures from the development of Northern Ghana in the short run. On the contrary, attention should be paid to the quality of migration, which will entail strengthening social protection mechanisms to reduce negative migration, and raising human capital while increasing the absorptive capacities of cities to encourage positive migration. This migration to the South will further benefit the North, since migrants will add to the pool of remittances sent to Northern Ghana.